1997
DOI: 10.1099/00207713-47-3-622
|View full text |Cite
|
Sign up to set email alerts
|

Thermococcus hydrothermalis sp. nov., a New Hyperthermophilic Archaeon Isolated from a Deep-Sea Hydrothermal Vent

Abstract: An extremely thermophilic archaeon, strain AL662T, was isolated from a deep-sea hydrothermal vent located on the East Pacific Rise at a latitude of 21"N. This strain is a strictly anaerobic coccus, and its cells range from 0.8 to 2 pm in diameter. The optimum temperature, pH, and Sea Salt concentration for growth are 85"C, 6, and 20 to 40 g/liter, respectively. Strain AL662T grows preferentially on proteolysis products, on a mixture of 20 amino acids, and on maltose in the presence of elemental sulfur. The mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
61
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 27 publications
1
61
0
1
Order By: Relevance
“…Furthermore, fluorescent 16S rDNA probes specific for the Aquificales and a novel sulfur-reducing lineage represented by Desulfurobacterium (Harmsen et al, Deep-sea microaerophilic thermophiles 1997) showed that up to 40 % of the bacterial community was accounted for by these lineages in a hydrothermal chimney from the Mid-Atlantic Ridge. It is therefore possible that, like their terrestrial relatives, the chemolithoautotrophic Aquificales are important members of high-temperature, deep-sea hydrothermal vent niches, providing organic carbon for deep-sea vent heterotrophs such as the Thermococcales (Canganella et al, 1998 ;Godfroy et al, 1996Godfroy et al, , 1997 and the Thermotogales (Takai & Horikoshi, 2000).…”
Section: Ecological Niche and Evolutionary Implicationsmentioning
confidence: 99%
“…Furthermore, fluorescent 16S rDNA probes specific for the Aquificales and a novel sulfur-reducing lineage represented by Desulfurobacterium (Harmsen et al, Deep-sea microaerophilic thermophiles 1997) showed that up to 40 % of the bacterial community was accounted for by these lineages in a hydrothermal chimney from the Mid-Atlantic Ridge. It is therefore possible that, like their terrestrial relatives, the chemolithoautotrophic Aquificales are important members of high-temperature, deep-sea hydrothermal vent niches, providing organic carbon for deep-sea vent heterotrophs such as the Thermococcales (Canganella et al, 1998 ;Godfroy et al, 1996Godfroy et al, , 1997 and the Thermotogales (Takai & Horikoshi, 2000).…”
Section: Ecological Niche and Evolutionary Implicationsmentioning
confidence: 99%
“…Members of the orders Thermococcales and Thermotogales are isolated most frequently and are widely distributed in global deep-sea hydrothermal systems (Pledger & Baross, 1989;1991;Stetter et al, 1990Stetter et al, , 1993Gonzalez et al, 1995Gonzalez et al, , 1998Godfroy et al, 1996Godfroy et al, , 1997Antoine et al, 1997;Takai & Fujiwara, 2002). Recently, several investigations using a combination of culture-dependent and -independent analyses have revealed that these sulfur-reducing, heterotrophic thermophiles dominate microbial populations in deep-sea hydrothermal vent chimney structures, specifically on the surfaces of the chimney structures (Harmsen et al, 1997;Takai et al, 2001).…”
mentioning
confidence: 99%
“…이것은 열수구에 존재하는 고세균 중 가장 우점하는 종류가 Thermococcus이기 때문으로 추정된다 (Takai and Nakamura, 2011). Thermococcus 속에 속하는 종들의 생장 온도는 약 55-110℃의 범위에서 생장이 가능하고 (Stetter, 1996;Godfroy et al, 1997;Kuwabara et al, 2005), 최적의 온도는 약 80-90℃이다 (Zillig et al, 1983;Kobayashi et al, 1994;González et al, 1995;Dirmeier et al, 1998) (Arab et al, 2000).…”
unclassified